Răspuns :
x² + 6x + 9 = ( x + 3)² ≠ 0 ; deci x ≠ - 3
x ∈ R \ { - 3}
b = 2· ( x³ + 1) · ( x +3) / ( x +3)² · ( x² - x +1 ) =
= 2 · ( x +1) · ( x² - x + 1) / ( x +3) · ( x² - x + 1)
= 2 · ( x + 1) / ( x + 3)
c. E ( - 1 /2) = 2 · ( - 1 /2 + 1) / ( -1 /2 + 3) = 2 / 5
d. 2 · ( x +1) / ( x + 3) ∈ N
2 · ( x + 3 - 2) / ( x +3) = 2 · [ ( x +3) / ( x +3) - 2 / ( x + 3) ] =
= 2 · [ 1 - 2 / ( x +3) ] ∈ N
daca x + 3 = 2 ; x = -1 E( -1) = 2 /2 =1
x + 3 = 1 ; x = -2 E(-2) =0
x + 3 = -2 ; x = -5 E( - 5) = 3
x + 3 = - 1 ; x = - 4 E(-4) = 4
x ∈ R \ { - 3}
b = 2· ( x³ + 1) · ( x +3) / ( x +3)² · ( x² - x +1 ) =
= 2 · ( x +1) · ( x² - x + 1) / ( x +3) · ( x² - x + 1)
= 2 · ( x + 1) / ( x + 3)
c. E ( - 1 /2) = 2 · ( - 1 /2 + 1) / ( -1 /2 + 3) = 2 / 5
d. 2 · ( x +1) / ( x + 3) ∈ N
2 · ( x + 3 - 2) / ( x +3) = 2 · [ ( x +3) / ( x +3) - 2 / ( x + 3) ] =
= 2 · [ 1 - 2 / ( x +3) ] ∈ N
daca x + 3 = 2 ; x = -1 E( -1) = 2 /2 =1
x + 3 = 1 ; x = -2 E(-2) =0
x + 3 = -2 ; x = -5 E( - 5) = 3
x + 3 = - 1 ; x = - 4 E(-4) = 4